1990
DOI: 10.1159/000261231
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Root Fluoride Uptake by Monocalcium Phosphate Monohydrate Gels

Abstract: Application of monocalcium phosphate monohydrate (MCPM) gel, which produces small amounts of dicalcium phosphate dihydrate in enamel, was previously shown to increase the enamel reactivity with fluoride (F). This study was conducted to determine whether the MCPM gel treatment is also effective in enhancing F uptake by root surfaces of human teeth. The results show that samples receiving daily treatments with MCPM gel for 10 min followed by immersion in a 1-ppm F solution for 5 days acquired a significantly gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1990
1990
1998
1998

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The precipitation of minerai should reduce the porosity of the enamel, which, as noted above, is desirable in terms of increasing the resistance against demineralization. Under comparable conditions, root cementum acquired even greater amounts of F. However, a portion of this F can be washed out by a calcium phosphate solution saturated with FAp (Takagi et al, 1989), suggesting that this more labile form of F is adsorbed onto the crystal surfaces and is not in apatitic form (Laufer et al, 1981). These studies showed that the firmly bound F content of teeth can be significantly increased by immersion in a F-containing calcium phosphate solution for several days.…”
Section: Methods Of Incorporating Tooth-bound F Into Sound Enamel Andmentioning
confidence: 72%
“…The precipitation of minerai should reduce the porosity of the enamel, which, as noted above, is desirable in terms of increasing the resistance against demineralization. Under comparable conditions, root cementum acquired even greater amounts of F. However, a portion of this F can be washed out by a calcium phosphate solution saturated with FAp (Takagi et al, 1989), suggesting that this more labile form of F is adsorbed onto the crystal surfaces and is not in apatitic form (Laufer et al, 1981). These studies showed that the firmly bound F content of teeth can be significantly increased by immersion in a F-containing calcium phosphate solution for several days.…”
Section: Methods Of Incorporating Tooth-bound F Into Sound Enamel Andmentioning
confidence: 72%
“…Takagi et al [1990] reported that the mean F content in the outer 10 pm of root dentin increased by about 2,570 pg of F per gram of dentin (ppm) when the specimens were immersed for 5 days in a pH 7 calcium phosphate-containing solution that also contained 52.6 pmol/1 (1 ppm) of F. Approximately 900 ppm of dentin of the incorporated F was labile, i.e., leachable into a solution similar to the washing solution used in the present study. If in the present study the F depo sition were estimated by root F biopsy instead of by F wash ing, the F deposition produced by a 1-min application o f the Na2SiF,,-CaCl2 two-solution rinse (3.25 pg/cm2) and the The means (± SD) o f any two groups connected by a vertical line are not significantly different (p>0.05; n = 35).…”
Section: F Uptake Studymentioning
confidence: 99%
“…Attin T., Buchalla W., Siewert C., Hellwig E. (1999): Fluoride release / uptake of polyacid modified resin composites (compomers) in neutral and acidic buffer solutions. J Oral Rehabil, 26 (5), 388-393.…”
Section: βιβλιογραφιαmentioning
confidence: 99%